Peningkatan Hasil Belajar IPS dengan Menggunakan model pembelajaran Role Playing pada Siswa Kelas IV Semester II SDN I Saradan Kecamatan Baturetno Kabupaten Wonogiri Tahun Pelajaran 2018/2019 - Nanang Sugiyanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to describe the social studies learning difficulties of fourth grade elementary school students of SDN 1 Saradan. Research data were collected through study analysis documents, interviews, and field notes. The method of analyzing this research data is by displaying test result notes containing analysis of test results and interpretation of note results. The results of data analysis show that students have difficulty in identifying various forms of ethnic, social, and cultural diversity in Indonesia that are bound by unity and integrity. From this study, it was found that the use of the Role Playing model can improve social studies learning outcomes in the 4th grade students of SDN 1 Saradan, which is marked by an increase in the learning process. By using the Role Playing model, it can improve learning outcomes. Identifying various forms of ethnic, social, and cultural diversity in Indonesia in the 4th grade Students of Semester II SDN I Saradan Baturetno, Wonogiri District, 2018/2019 Academic Year from the moderate category to the good category.This research can be used as a guide in minimizing social studies learning difficulties.